Effect of high-dose intravenous vitamin C therapy on the prognosis in patients with moderately severe and severe acute pancreatitis: protocol of a prospective, randomized, double-blinded, placebo-controlled study - Sun, Wenwu; Zhao, Bing; Li, Jiaoyan; Wang, Yihui; Qi, Xing; Ning, Ning; Sun, Silei; Li, Mengjiao; Yao, Yi; Ni, Tongtian; Ma, Li; He, Juan; et al. (Frontiers in Medicine, 2023)
Introduction Acute pancreatitis is a common gastrointestinal disease. The mortality of patients affected by severe acute pancreatitis (SAP) remains high. It is unclear whether high-dose intravenous vitamin C (HDIVC) therapy could improve the prognosis of these patients. The current prospective, randomized, double-blinded, placebo-controlled study will explore the effect of high-dose intravenous vitamin C therapy on the prognosis in patients with moderately severe and severe acute pancreatitis. Methods and design A total of 418 participants with moderately severe and severe acute pancreatitis who meet the eligible criteria will be randomly assigned in a 1:1 ratio to receive treatment with HDIVC (200 mg/kg/24 h) or placebo (saline) for a period of 7 days. The primary outcome is 28-day mortality in these patients. The secondary outcomes include organ functions and interventions, laboratory tests, healthcare, and 90-day mortality. Ethics and dissemination This protocol was approved by the institutional ethics board of the Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, China (Registration Number: 2019-90). The report of the study will be published in peer-reviewed journals and presented at conferences, both nationally and internationally. Clinical trial registration Chinese Clinical Trial Registry (ChiCTR1900022022). Version 1.5.